(untitled) (Pravaha, 2020)
Management control system is to provide information that is useful for managerial decision-making, planning, monitoring and evaluation of organizational activities to alter employee behavior. The main purpose of the study is to show the effect of MCS on perceived performance of Nepalese commercial Banks. This study followed the descriptive and inferential statistics. Descriptive and analytical research design has been used. As per the descriptive statistics most of the respondent were agreed that MCS has increased the perceived performance of commercial Banks. There exists strong correlation among the dependent and independent variables. The correlation is statistically significant at 1 percent level of significant.